Investigating family members’ experiences of the implementation and effectiveness of a youth-focused suicide aftercare service: a qualitative study - Marianne Webb; Hannah Richards; Michelle Lamblin; Dzenana Kartal; Pemma Davies; Natasha Swingler; Jo Robinson (BMC Health Services Research)
Abstract Background Aftercare services bridge the gap between hospital-based care following a suicidal crisis and ongoing support in the community. Family members can have a critical role in supporting a young person after a suicidal crisis, acting as care managers, responsible for keeping young people safe, and navigating the mental health system. This study aimed to investigate family members’ experience of the implementation and effectiveness of a youth-focussed aftercare service. Methods We conducted semi-structured interviews with 10 parents of a young person who had been discharged from a youth-focused assertive suicide aftercare service, guided by the Research, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework. We used Applied Thematic Analysis to conduct a hybrid deductive-inductive analysis on transcribed interviews. Results Eight themes were generated from the thematic analysis: (1) Referral process can be opaque and difficult to navigate; (2) Logistics and costs can be a barrier; (3) Increasing knowledge and skills improves family functioning; (4) The impact on young people’s mental health and functioning – building a solid foundation; (5) Regular and transparent communication with staff facilitates engagement; (6) Family and peer sessions provide valuable support, insights, and skills; (7) Individually tailored program meets the needs of most young people; and (8) Discharge process can be inconsistent and unsupportive. Conclusions Overall, the youth aftercare service met the needs of family members, who report significant improvements in family functioning and mental health. Key areas for improvement are the referral and discharge processes, which were often opaque and burdensome. Our findings highlight the importance of addressing family context and needs within youth aftercare services, and ensuring there are sufficient resources to provide family-focused interventions.